The science of Agatha Christie : the truth behind Hercule Poirot, Miss Marple, and more iconic characters from the Queen of Crime - Hafdahl, Meg; Florence, Kelly (Skyhorse Publishing, 2023)
Gothic media moguls Meg Hafdahl and Kelly Florence, authors of The Science of Stephen King and co-hosts of the Horror Rewind podcast called "the best horror film podcast out there" by Film Daddy, present a guide to the Agatha Christie stories and supersleuths we all know and love. Through interviews, literary and film analysis, and bone-chillling discoveries, The Science of Agatha Christie uncovers the science behind the sixty-six detective novels and fourteen short story collections that have become an integral part of the modern murder mystery, answering such questions as: What is the science behind the poisons used to commit murders in Agatha Christie's stories? When did crime investigation become more common as seen in Murder on the Orient Express? Has science made it possible to uncover the truth behind the investigative powers of Hercule Poirot and Miss Marple? Join Kelly and Meg as they discover why sometimes the impossible must be possible!